ChemInform Abstract: Visible Light‐Induced Iodine‐Catalyzed Transformation of Terminal Alkynes to Primary Amides via CC Bond Cleavage under Aqueous Conditions. Issue 25 (June 2016) - Dighe, Shashikant U.; Batra, Sanjay
Abstract: This metal‐free protocol, which ensues via initial hydroamination of the acetylene bond, followed by release of CH2 I2, is suitable for aromatic, heteroaromatic, and aliphatic alkynes.